Synthesis novel N,S-substituted nitrobutadiene derivatives: some metabolic enzyme inhibition properties and antioxidant activities and in silico ADMET and molecular docking studies - Bayrak, Bertan Boran; Ertik, Onur; Onul, Nihal; Mermer, Nese Senturk; Yanardag, Refiye (Springer, 2024)
Enzyme inhibition is one of the leading drug development methods for the treatment of many diseases. Due to the possible side effects and low bioavailability of existing drugs, studies are continuing for the discovery of new drugs. In this study, in vitro elastase, acetylcholinesterase inhibition activities of newly synthesized N,S-substituted polyhalogenated nitrobuta-1,3-dienes derivatives (compounds 3, 4a, 4b, 4c, 4d, 4e, and 4f), as well as their antioxidant properties, were investigated. Results was showed that compounds 4a (IC50 = 22.10 +/- 0.49 mu M), 4b (IC50 = 53.98 +/- 1.77 mu M), and 4f (IC50 = 32.01 +/- 1.33 mu M) showed higher elastase inhibition effect than positive control, ursolic acid (IC50 = 479.11 +/- 15.53 mu M) and in silico adsorption, distribution, metabolism, excretion, and toxicity (ADMET) and molecular docking studies were carried out in line with the results. As a result of molecular docking studies with iGemdock, DockThor, and Autodock Vina, it was determined that there was a higher binding relevance for compounds 4a (- 84.41/- 8.439 kcal/mol), 4b (- 86.32/- 7.878 kcal/mol), and 4f (- 86.32/- 8.530 kcal/mol) than ursolic acid (- 77.67/- 7.024 kcal/mol) for iGemdock and DockThor. It has been shown by DPPH, ABTS, and reducing power experiments that all compounds also show antioxidant properties. In conclusion, both in vitro and in silico molecular docking studies of compounds 4a, 4b, and 4f show that these three compounds are potent inhibitors of elastase.
Keywords: Nitrobutadienes; Elastase; Acetylcholinesterase; Antioxidant; Molecular docking